Hygienic estimation of occupational risk and substantiation of regulations on Orvego Fungicide safe application in agricultural sector - Bilous S.V.; Vavrinevych E.P.; Omelchuk S.T. (Medičnì Perspektivi, 2015)
Hygienic evaluation of labour conditions during Orvego pesticide application on grapes and onion was carried out and content of ametoctradin and dimethomorp in the working zone air, atmospheric air, and the soil was studied. The findings allow to substantiate ametoctradin hygienic standards in the working zone air, atmospheric air, and the soil and to elaborate regulations of Orvego pesticide safe application in agriculture. Estimation of complex risk of ametoctradin and dimethomorp effects via different routes of exposure during airblast and boom spraying treatment showed that the values of the risks were within the ranges of allowable (<1). Values of combined risk during simultaneous effect of the both active ingredients do not exceed allowable level (<1) either.